2022
DOI: 10.1111/bjet.13196
|View full text |Cite
|
Sign up to set email alerts
|

A motivational model‐based virtual reality approach to prompting learners' sense of presence, learning achievements, and higher‐order thinking in professional safety training

Abstract: Increasing learners' sense of presence is important in professional training, in particular, when aiming to foster their competences of making judgements and solving problems when facing real cases. However, in conventional training programmes, sometimes it is difficult to situate learners in real cases owing to several considerations, such as cost and potential danger. Scholars have indicated that the lack of opportunities to experience real contexts could seriously affect the training outcomes. To cope with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The element of confidence mainly involves expectations, self-confidence, and learning requirements, whereas the satisfaction factor is primed by avoiding negative thoughts, expecting natural consequences, and hoping for unexpected rewards and positive outcomes (Issac and Issac, 2020; Labafi et al ., 2021). Current studies using the ARCS model underscore its importance by revealing that techniques based on this model can enhance learners' sense of presence, critical thinking awareness, and problem-solving tendencies (Hwang et al ., 2022). Mindfulness unequivocally enhances these critical factors, which enables the successful completion of all knowledge management-related activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The element of confidence mainly involves expectations, self-confidence, and learning requirements, whereas the satisfaction factor is primed by avoiding negative thoughts, expecting natural consequences, and hoping for unexpected rewards and positive outcomes (Issac and Issac, 2020; Labafi et al ., 2021). Current studies using the ARCS model underscore its importance by revealing that techniques based on this model can enhance learners' sense of presence, critical thinking awareness, and problem-solving tendencies (Hwang et al ., 2022). Mindfulness unequivocally enhances these critical factors, which enables the successful completion of all knowledge management-related activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In (Chang & Hwang, 2021;Hwang et al, 2022). The effectiveness of VR-based training in improving occupants' response and preparedness for active shooter incidents is yet to be justified.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Furthermore, future experiments can investigate other training approaches (e.g., VR‐based training). Previous studies have demonstrated the outperformance of VR‐based training over traditional training methods in promoting professional skills in nursing staff (Chang & Hwang, 2021; Hwang et al, 2022). The effectiveness of VR‐based training in improving occupants' response and preparedness for active shooter incidents is yet to be justified.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…However, in traditional physics, it can be difficult to place learners in real task scenarios, mainly due to cost and risk factors. A lack of experience in real‐world settings can seriously affect learning outcomes (Hwang et al, 2022). In the process of constructing knowledge, three levels in the initial cognitive stages (knowledge, comprehension and application) (Bloom & Krathwohl, 1956) should be developed gradually.…”
Section: Literature Reviewmentioning
confidence: 99%